A decision-making support system for low-density traffic railway lines management - Pieriegud, Jana (Univerzita Pardubice, 2010)
In recent years, the issue of closing down or revitalisation of low-density traffic railway lines in Poland has become increasingly important. These decisions are usually taken without undertaking precise analysis, due to the difficulties inherent in cost calculation. Furthermore a distinguishing feature of this category of lines is that budget limitations and low profits are more critical factors than travel time and traffic frequency. The paper outlines the main assumptions for the establishment of a software-based system that will support the decision-making processes concerning the revitali-zation of existing low-density lines, its maintenance and operation management. The system, which can be useful for infrastructure managers, railway operators as well as local authorities, is currently being developed within the R&D project undertaken in Poland in 2008.
Keywords: low-density traffic railway lines; modelling transport system; decision-making support; maintenance; cost calculation model